2021
DOI: 10.3389/fimmu.2021.635899
|View full text |Cite
|
Sign up to set email alerts
|

Flipside of the Coin: Iron Deficiency and Colorectal Cancer

Abstract: Iron deficiency, with or without anemia, is the most frequent hematological manifestation in individuals with cancer, and is especially common in patients with colorectal cancer. Iron is a vital micronutrient that plays an essential role in many biological functions, in the context of which it has been found to be intimately linked to cancer biology. To date, however, whereas a large number of studies have comprehensively investigated and reviewed the effects of excess iron on cancer initiation and progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 177 publications
(265 reference statements)
0
39
0
Order By: Relevance
“…Contrastingly, increasing evidence suggests that patients with HF have an increased risk of developing cancer [ 163 , 164 , 170 ]. Interestingly, iron has emerged as a potential cause for tumorigenesis, especially in colorectal cancer [ 171 , 172 , 173 , 174 ]. The contribution of ID to the incidence of cancer in HF patients is not yet elucidated and worth further investigation.…”
Section: Causes Of Iron Deficiency In Heart Failurementioning
confidence: 99%
“…Contrastingly, increasing evidence suggests that patients with HF have an increased risk of developing cancer [ 163 , 164 , 170 ]. Interestingly, iron has emerged as a potential cause for tumorigenesis, especially in colorectal cancer [ 171 , 172 , 173 , 174 ]. The contribution of ID to the incidence of cancer in HF patients is not yet elucidated and worth further investigation.…”
Section: Causes Of Iron Deficiency In Heart Failurementioning
confidence: 99%
“…Thus, there appeared to be an iron-deficiency-specific effect on the development of mammary cancer. We judge that this is important for population studies since previous cycles of publications suggested that future studies of iron–cancer hypotheses are likely to be reported, if not in breast then minimally in other organ sites [ 62 ]. The more meaningful effects of either low or high iron status on cancer risk should be assessed by making the referent group chosen for comparison be the iron-adequate group, as judged using clinical standards of iron status assessment.…”
Section: Resultsmentioning
confidence: 99%
“…In this setting, GI MΦ are of particular importance, since they are major local producers of cytokines, thus creating the inflammatory microenvironment [45][46][47], and they are also the main iron-retaining cells due to downregulation of the iron exporter FPN1 under inflammation [36,48]. Moreover, impairment of the immune response has been reported both during iron deficiency and overload (reviewed in [49,50]), likely reflecting a narrow range for cellular iron levels promoting proper immune responses, which may have consequences for MΦ immunosurveillance. In fact, several studies have described a link between Helicobacter pylori stomach infection and iron-deficiency anemia [51][52][53], but a clear physiological mechanism and potential relationship with MΦ iron handling remains unexplained.…”
Section: Gut Mφmentioning
confidence: 99%